Pengaruh Faktor Psikologis, Sosial dan Finansial terhadap Kepuasan Kerja Guru MAN Kabupaten Bireuen - Abidah, Abidah; Syaripuddin, Syaripuddin (Aceh Cooperative Care, 2023)
This research aims to analyze the influence of psychological, social and financial factors on job satisfaction using case studies on 183 State Madrasah Aliyah (MAN) teachers in Bireuen Regency. This research takes the form of a survey with a questionnaire instrument as a data collection tool, using associative descriptive research. Problem analysis through a statistical approach, namely the path analysis model. The results of the research show that (1) there is a causal relationship between psychological and social factors of 0.593, (2) there is a causal relationship between social and financial factors of 0.562, (3) there is a causal relationship between teacher finances and psychological factors of 0.514. So the magnitude: (a) the direct and indirect influence of psychological factors on teacher job satisfaction is 50.2%, (b) the direct and indirect influence of social factors on teacher job satisfaction is 48.3%, and (c) the direct and Indirect financial factors on teacher job satisfaction were 53.38%. Apart from that (d), it can be seen that the influence of psychological, social and financial factors together on the job satisfaction of MAN teachers in Bireuen Regency is 61%.